The Effect of PjBL STEM Learning on Students' Systems Thinking Skills on Alternative Energy Materials - Habibah, Hulwah; Lidya, Nala; Suryadi, Ahmad (Universitas Lambung Mangkurat, 2024)
This study explores the effect of project-based learning (PBL) integrated with STEM on improving students' systemic thinking abilities. The study employed a quasi-experimental pretest-posttest control group design as its research method. The population consisted of 244 students enrolled in the tenth grade during the odd semester of the 2023-2024 academic year, and participants involved in the study were 68 tenth-grade students from one of the Islamic Senior High Schools of the State in Jakarta. The experimental group used PjBL STEM, while the control class used 5E learning (engagement, exploration, explanation, elaboration, and evaluation). The researcher developed a system thinking instrument adapted from Melinda based on pre-requirement, basic, intermediate, and coherent expert levels. In this study, data analysis used the non-parametric Mann-Whitney U test and Wilcoxon test. The research findings indicate a significant improvement in the system thinking ability of the experimental group students, while the control group's system thinking ability did not improve significantly. The results showed that the effect of PjBL STEM improvement in the experimental class was 0.54 (effect size) on students' systems thinking ability but was still in the low category and did not improve either in the control class. In addition, the level of systems thinking increased in the expert category, while the intermediate level did not increase. This study can be a reference for further research investigating the effect of PjBL STEM on students' systems thinking in different contexts.